2009
DOI: 10.4103/0250-474x.58192
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous RP-HPLC estimation of trifluoperazine hydrochloride and chlordiazepoxide in tablet dosage forms

Abstract: A binary mixture of trifluoperazine HCl and chlordiazepoxide was determined using reversed-phase liquid chromatography method using methanol:water (97:03, v/v) pumped at a flow rate of 1.0 ml/min. Quantification was achieved with ultraviolet detection at 262 nm over concentration ranges of 0.1-1 and 0.5-5 μg/ml; mean accuracies were 101.05±0.47 and 98.97±0.33 %, respectively. The method was successively applied to tablet dosage forms as no chromatographic interferences from the tablet excipients were observed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Concerning the limit of detection for the drug TFPH, our finding was in harmony with that obtained by Karimi et al [20] using indirect spectrophotometric method and principal component regression (PCR), partial least squares (PLS) and orthogonal signal correction (OSC)-PLS multivariate calibration methods and was 8-fold better better than that obtained by Navyasri et al [12] and 2-fold better than that obtained by Pattanayak and Ash Rani [11] whom using RP-HPLC method. However, it was worse than that obtained by Sharma etal [6] Patel and Patel [7], Parvataneni and Nagarjuna [13] using the developed RP-HPLC, and Waleed [4] using indirect flame AAS. Regarding the detection limit of vanadium, it observed that it was not good as with those obtained by Liu and Jiang [32], Okamoto et al [35] and Khammas et al [37] whom used more sophisticated instrumentation such as ICP-MS, ETA-ICP-OES and CPE-spectrophotometry using newly prepared organic reagent, respectively.…”
Section: Calibration Curves For Tfph Drug and V(v) Ionsmentioning
confidence: 62%
See 1 more Smart Citation
“…Concerning the limit of detection for the drug TFPH, our finding was in harmony with that obtained by Karimi et al [20] using indirect spectrophotometric method and principal component regression (PCR), partial least squares (PLS) and orthogonal signal correction (OSC)-PLS multivariate calibration methods and was 8-fold better better than that obtained by Navyasri et al [12] and 2-fold better than that obtained by Pattanayak and Ash Rani [11] whom using RP-HPLC method. However, it was worse than that obtained by Sharma etal [6] Patel and Patel [7], Parvataneni and Nagarjuna [13] using the developed RP-HPLC, and Waleed [4] using indirect flame AAS. Regarding the detection limit of vanadium, it observed that it was not good as with those obtained by Liu and Jiang [32], Okamoto et al [35] and Khammas et al [37] whom used more sophisticated instrumentation such as ICP-MS, ETA-ICP-OES and CPE-spectrophotometry using newly prepared organic reagent, respectively.…”
Section: Calibration Curves For Tfph Drug and V(v) Ionsmentioning
confidence: 62%
“…Vanadium (V) Ions in Real Matrices by Visible Spectrophotometry After Cloud Point Extraction TFFH is subjected to many research works, either for the development of the methods of its determination in pure form and pharmaceuticals or as chromogenic reagent for estimation of various target analytes. The literature survey reveals that a number of analytical methods for detection of this drug individually or in combination with other drugs have been used including, indirect atomic absorption spectrometry [4], potentiometry [5], reverse phase high performance liquid chromatography (RP-HPLC) [6][7][8][9][10][11][12][13], solid-phase extraction-high performance liquid chromatography (SPE-HPLC) [14], liquid chromatography -mass spectrometry / mass spectrometry (LC-MS/MS) [15] densitometry [16] and spectrophotometry [17][18][19][20]. Also, this drug was proposed as a chelating agent for the determination of some metal ions like Cr +6 [21], Tl 3+ [22], Fe 3+ [23] ions.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] A few other analytical methods have been reported with trifluoperazine and isopropamide simultaneously, individually and with other drugs. [17][18][19][20][21][22] So far no simultaneous spectrophotometric method has been reported with this combination and hence forms the basis of the present work.…”
Section: Original Articlementioning
confidence: 99%
“…A literature survey has revealed several analytical methods for the determination of CHL either alone or in mixtures with other drugs [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%